Pollinic characterization of Raulinoa echinata R. S. Cowan (Rutaceae), Dyckia brevifolia Baker and Dyckia ibiramensis Reitz (Bromeliaceae), reophyte and saxicolous endemic species of river Itajaí-Açu, Santa Catarina, Brazil - Denise Monique Dubet da Silva Mouga; Bruna Tereza Possamai; Enderlei Dec; Sílvio Murilo Cristóvão da Silva (Acta Biológica Catarinense, 2017)
Aiming to contribute with elements about the reproduction of the reophytes Raulinoa echinata, Dyckia brevifolia and Dyckia ibiramensis as well as to support their taxonomic definition, their pollinic characterization was carried out. Fresh pollen grains were prepared by acetolysis. Observations occurred on a light microscope and a scanning electron microscope. Measures were done of the polar (P) and equatorial diameters (E) and thickness of the exine and are expressed as means in micrometers. R. echinata: monad; radial symmetry; medium size; P=49,07±3,33; E=33,95±3,94; prolate (ratio P / E); ambitus subtriangular; 3-aperturated with long colpi and lalongate endoapertures; exine striated with thickness 1.54 ± 0,32. Dyckia brevifolia: monad; bilateral symmetry; medium size; P=25,16 ± 3,02; E=43,16±3,50 x 28,12±3,26; ambitus elliptical; monoaperturated with one long sulcus; exine reticulate with thickness 1,66 ± 0,31. D. ibiramensis: monad; bilateral symmetry; medium size; P=29,54±3,17; E=42,36±3,60 x 28,43±3,38; ambitus elliptical; monoaperturated with one long sulcus; exine reticulate with thickness 1,73 ± 0,28. Data obtained can allow to verify hydrophily for the three species as well as suggest Raulinoa proximity with Metrodorea and Esenbeckia (both Pilocarpinae) and confirm D. brevifolia e D. ibiramensis to Pitcairnioideae.